2018
DOI: 10.1038/s41598-018-23788-3
|View full text |Cite
|
Sign up to set email alerts
|

Temperature induced crossing in the optical bandgap of mono and bilayer MoS2 on SiO2

Abstract: Photoluminescence measurements in mono- and bilayer-MoS2 on SiO2 were undertaken to determine the thermal effect of the MoS2/SiO2 interface on the optical bandgap. The energy and intensity of the photoluminescence from monolayer MoS2 were lower and weaker than those from bilayer MoS2 at low temperatures, whilst the opposite was true at high temperatures above 200 K. Density functional theory calculations suggest that the observed optical bandgap crossover is caused by a weaker substrate coupling to the bilayer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…9(d) we compare our calculated temperaturedependent band gap of MoS 2 (green) with experimental data from Ref. [96] (black). To facilitate comparison we introduced a scissor correction of 0.34 eV to match the measured band gap at 4 K. This correction is similar to that obtained using GW and the Bethe-Salpeter equation (BSE) [97].…”
Section: Summary Of Procedures and Numerical Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…9(d) we compare our calculated temperaturedependent band gap of MoS 2 (green) with experimental data from Ref. [96] (black). To facilitate comparison we introduced a scissor correction of 0.34 eV to match the measured band gap at 4 K. This correction is similar to that obtained using GW and the Bethe-Salpeter equation (BSE) [97].…”
Section: Summary Of Procedures and Numerical Resultsmentioning
confidence: 96%
“…We show the results of the special displacement method (green circles) and experimental data from Ref. [96] (black triangles). The calculated band gaps were scissor-shifted by 0.34 eV to match the experimental value at 4 K. The straight line is the high-temperature limit and intercepts the T = 0 K axis at the clamped-ion band gap (1.93 eV, empty circle).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been established in many experimental and theoretical works [ 2 , 5 , 14 , 15 , 18 , 38 , 40 , 41 ] that MoS 2 remains an indirect semiconductor even when reduced to bilayers. Observation of the indirect-gap emission around 1.25 eV on 3 nm-thick MoS 2 ( Figure 3 ) has revealed that MoS 2 retains its indirect characteristics even when its thickness is reduced to just four layers.…”
Section: Resultsmentioning
confidence: 99%